EXTRACTION AND IDENTIFICATION OF ENDOPHYTIC BACTERIA FROM BAMBOO PLANTS (PHYLLOSTACHYS AND FARGESIA) - О. В. Мошинець; Ж. Бруне; С. Ю. Римар; I. В. Косаківська; Г. Потерс (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
Endophytic bacteria from rhizomes and culms of bamboo plants (Bambusoideae) have been identified by the way of DNA extraction from both plant tissues and isolated bacterial cultures and subsequent determination of the rrs (16S rDNA) sequences. 74 endophytic strains have been isolated thus far, leading to the identification of 47 unique species, belonging to the families Bacillaceae, Mycobacteriaceae, Paenibacillaceae and Microbacteriaceae and the genera Agrobacterium, Rhizobium, Burkholderia, Pseudomonas, Leifsonia, Achromobacter and Acinetobacter.